(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The increasing use of mobile applications has profoundly influenced various facets of human progress, including the medical area. Electronic applications have demonstrated their ability to improve healthcare, monitor disease progression and serve as a constant stimulus for medication compliance in people with polypathology. Bringing multiple advantages in monitoring medication consumption in older adults who often suffer from cognitive disorders. To determine the importance of the use of mobile applications as a medication aid in the older adult. The search was conducted in Scopus, Pubmed and Ovid, using terms such as "Technology", "mobile applications", "medication system", "medication in older adult", with a maximum age of 5 years. Mobile applications are valuable in improving medication adherence, particularly among the older adult population, depending on the method of engagement, whether through personal interaction, email or telephone means, and on the regularity of dispensing and the intended therapeutic target. Mobile applications improve medication adherence for various chronic diseases in older adults, in direct relation to the quality and quantity of medication and the sociodemographic characteristics of the patient, which favors medication recall.